A comprehensive investigation of hydrothermal carbonization: Energy potential of hydrochar derived from Virginia mallow. (August 2020) - Śliz, Maciej; Wilk, Małgorzata
Abstract: In this study, the effects of temperature, residence time and biomass to water ratio on hydrothermal carbonization of Virginia mallow were conducted. The main goal of this research was to investigate hydrochars derived from Virginia mallow in order to assess their fuel properties. Proximate, ultimate and high heating value analyses were used to establish the chemical energy content of raw biomass and hydrochars. TGA, SEM, BET and FTIR were performed to discuss the combustion characteristics and changes in the surface of the material. Temperature was found to be the main factor influencing the conversion of Virginia mallow during the HTC process. It was confirmed by the properties of hydrochar derived at 220 °C for 5 min which was as carbonaceous (51.8% carbon content) and reactive as that obtained at 200 °C for 60 min (52.5% carbon content). A sample pretreated at 200 °C for 90 min had the highest fixed carbon value (16.29%) when compared to raw feedstock (5.63%). In the resulting reduction of mass found in the hydrochar, an increase in the energy densification ratio as well as better combustion stability were also observed. Detailed analysis of the Results confirmed that the HTC is a promising method for producing energy-dense solid biofuel. Highlights: HTC of Virginia mallow at 180, 200, 220 °C and 5, 30, 60, 90, 240 min were studied. Impact of residence time, water to biomass ratio and temperature was discussed. Upgrading of hydrochars, energy and mass yields were determined. Fuel combustion performances by TGA and combustibility indexes were illustrated. SEM and FTIR Results underlined the strong impact of temperature.